ANALISIS PENUGASAN KARYAWAN BAGIAN PRODUKSI PADA CV. FAUZAN RAMADHAN DI MUARA BADAK - Agustian, Fery (EKONOMIA, 2012)
The study was conducted on CV.FAUZAN RAMADHAN in Muara Rhinos during the month of April-May 2012. Of this research in the data obtained that the decay has occurred black shrimp ranges 20-30 kg were produced. This decay occurs because the processing of the raw materials of black shrimp resolved differently in processing time starts at 07.30 am and finish at around 09:30 to 10:00 am.Analysis using the Hungarian method calculation results show after held assignments on the production employees in particular sub-section processing variations 5 working group (Task: Cleaning, Proofreading, washing, weighing and preparation) obtained by Hungarian method of processing turnaround time of 120 minutes is lower than the standard settlement time from 5 companies to task group working group variation in the amount of 150 minutes.